Avidity of anti-malarial antibodies inversely related to transmission intensity at three sites in Uganda. (December 2017) - Ssewanyana, Isaac; Arinaitwe, Emmanuel; Nankabirwa, Joaniter; Yeka, Adoke; Sullivan, Richard; Kamya, Moses; Rosenthal, Philip; Dorsey, Grant; Mayanja-Kizza, Harriet; Drakeley, Chris; Greenhouse, Bryan; Tetteh, Kevin
Abstract Background People living in malaria endemic areas acquire protection from severe malaria quickly, but protection from clinical disease and control of parasitaemia is acquired only after many years of repeated infections. Antibodies play a central role in protection from clinical disease; however, protective antibodies are slow to develop. This study sought to investigate the influence ofPlasmodium falciparum exposure on the acquisition of high-avidity antibodies toP. falciparum antigens, which may be associated with protection. Methods Cross-sectional surveys were performed in children and adults at three sites in Uganda with variedP. falciparum transmission intensity (entomological inoculation rates; 3.8, 26.6, and 125 infectious bites per person per year). Sandwich ELISA was used to measure antibody responses to twoP. falciparum merozoite surface antigens: merozoite surface protein 1-19 (MSP1-19) and apical membrane antigen 1 (AMA1). In individuals with detectable antibody levels, guanidine hydrochloride (GuHCl) was added to measure the relative avidity of antibody responses by ELISA. Results Within a site, there were no significant differences in median antibody levels between the three age groups. Between sites, median antibody levels were generally higher in the higher transmission sites, with differences more apparent for AMA-1 and in ≥5 year group. Similarly, median avidity index (proportion of high avidity antibodies) showed no significant increase with increasing age but was significantly lower at sites of higher transmission amongst participants ≥5 years of age. Using 5 M GuHCl, the median avidity indices in the ≥5 year group at the highest and lowest transmission sites were 19.9 and 26.8, respectively (p = 0.0002) for MSP1-19 and 12.2 and 17.2 (p = 0.0007) for AMA1. Conclusion Avidity to two differentP. falciparum antigens was lower in areas of high transmission intensity compared to areas with lower transmission. Appreciation of the mechanisms behind these findings as well as their clinical consequences will require additional investigation, ideally utilizing longitudinal data and investigation of a broader array of responses.